Going to the Dentist - Civardi, Anne; Illustrated by Cartwright, Stephen (London Usborne, 1992)
Going to the dentist can be a scary experience, but this friendly book shows children what to expect. Stephen Cartwright's gentle illustrations are full of things for children to look at and talk about. Includes audio and simple text for children to read themselves, and a little yellow duck to spot on every page.
Include Color Illustrations
Keywords: Physicians -- Medical Fiction -- Children--Medical Examinations